2003
DOI: 10.1152/japplphysiol.00108.2002
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of exercise on tissue sensitivity to glucocorticoids

Abstract: The aim of this study was to address the effect of endurance training on tissue sensitivity to glucocorticoids (GC) in both resting and exercising conditions. In vitro dexamethasone inhibition of LPS-induced interleukin-6 secretion in cultures of peripheral monocytes was compared in untrained subjects (UT) and in endurance-trained men (ET) at the end of a 2-h run and during exercise recovery. We demonstrated an in vitro plasticity of sensitivity of monocytes to GC in ET men, superimposed to changes in systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
111
3
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 24 publications
9
111
3
4
Order By: Relevance
“…For example, the HPA adaptation to normal training is characterised by increased ACTH/cortisol ratio only during exercise recovery (due to decreased pituitary sensitivity to cortisol) (Lehmann et al 1993b;Duclos et al 1997Duclos et al , 1998, and by modulation REVISION : Consensus Statement "Overtraining" (17-07-2012) 10 of tissue sensitivity to glucocorticoids (Duclos et al 1999(Duclos et al , 2003). However, it should be emphasized that during a resting day, in endurance-trained athletes 24 h cortisol secretion under non-exercising conditions is normal Duclos et al 1999Duclos et al , 2003. Accordingly, morning plasma cortisol concentration and 24 h urinary free cortisol (UFC) excretion in resting endurance-trained men are similar to those of age-matched sedentary subjects (Kern et al 1995;Duclos et al 1997;Gouarne et al 2005).…”
Section: Biochemistry and Hormones Biochemistrymentioning
confidence: 99%
“…For example, the HPA adaptation to normal training is characterised by increased ACTH/cortisol ratio only during exercise recovery (due to decreased pituitary sensitivity to cortisol) (Lehmann et al 1993b;Duclos et al 1997Duclos et al , 1998, and by modulation REVISION : Consensus Statement "Overtraining" (17-07-2012) 10 of tissue sensitivity to glucocorticoids (Duclos et al 1999(Duclos et al , 2003). However, it should be emphasized that during a resting day, in endurance-trained athletes 24 h cortisol secretion under non-exercising conditions is normal Duclos et al 1999Duclos et al , 2003. Accordingly, morning plasma cortisol concentration and 24 h urinary free cortisol (UFC) excretion in resting endurance-trained men are similar to those of age-matched sedentary subjects (Kern et al 1995;Duclos et al 1997;Gouarne et al 2005).…”
Section: Biochemistry and Hormones Biochemistrymentioning
confidence: 99%
“…Following mental stress, the sensitivity of the immune system to dexamethasone inhibition (a synthetic version of the hormone cortisol that has potent anti-14 inflammatory properties) is reduced, as manifest by a reduction in this hormone's capacity to suppress the production of inflammatory cytokines (58). In endurance trained individuals, however, an acute bout of exercise has been shown to increase tissue sensitivity to glucocorticoids (59). HPA axis dysregulation and cortisol hypersecretion has been implicated in adverse mental health and cardiovascular outcomes.…”
Section: Physical Activity Stress and Inflammationmentioning
confidence: 99%
“…[16][17][18] Cortisol is a glucocorticoid secreted by the adrenal cortex and among other functions, increases glyconeogenesis and promotes fat mobilization and utilization. 19,20 Zinc also plays an important role in appetite regulation and may thus be expected to act as a mediator of leptin effects. 21 Studies 17,22,23 have shown low leptin levels in states of zinc deficiency.…”
Section: Introductionmentioning
confidence: 99%